Profile of Psychological Flexibility Among Students at MA Hidayatul Mubtadiin - Mariyana Eka Putri; Alrefi Alrefi; Dwi Septia Ningsih; Sonya Antika (Journal of Society Counseling, 2026)
This study aims to determine the psychological flexibility profiles of students at MA Hidayatul Mubtadiin. The study employed a quantitative approach using descriptive methods and involved 81 11th-grade students. Data were collected using a psychological flexibility scale that measures six aspects: acceptance, cognitive defusion, contact with the present moment, self as context, values, and committed action. Of the 30 items tested, 26 were found to be valid and reliable. Data analysis was conducted using descriptive statistics, specifically frequency and percentage. The results of the study indicate that the students’ psychological flexibility falls into the moderate category, followed by the high category, low, very low, and very high. These findings indicate that the majority of students already possess fairly good abilities to accept experiences, adapt to various situations, and act in accordance with their values, although further development efforts are still needed so that these abilities can develop optimally.